1995
DOI: 10.2307/2410278
|View full text |Cite
|
Sign up to set email alerts
|

Floral Correlates and Fitness Consequences of Mating-System Variation in Turnera ulmifolia

Abstract: Outcrossing rates varied from 0% to 69% among Jamaican populations of Turnera ulmifolia. A correlation between increasing herkogamy and outcrossing rate occurred among populations. Predictions from sex‐allocation theory were tested by estimating allocation to reproductive functions. Significant differences in allocation patterns occurred among populations, but they were not correlated with outcrossing rates. The fitness consequences of inbreeding were assessed in high‐ and low‐density greenhouse experiments fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 40 publications
3
77
0
Order By: Relevance
“…Several authors have demonstrated that pollinator-mediated selection might play an important role in floral trait evolution in animal-pollinated species (Stanton et al,1986 ;Galen, 1989 ;Robertson & Wyatt, 1990). In this context there has been much interest in the adaptive significance of variation in stigma position, owing to the effect of this trait on pollen receipt and maternal fecundity (Campbell et al, 1994 ;Belaoussoff & Shore, 1995 ;Armbruster, 1996).…”
Section: mentioning
confidence: 99%
“…Several authors have demonstrated that pollinator-mediated selection might play an important role in floral trait evolution in animal-pollinated species (Stanton et al,1986 ;Galen, 1989 ;Robertson & Wyatt, 1990). In this context there has been much interest in the adaptive significance of variation in stigma position, owing to the effect of this trait on pollen receipt and maternal fecundity (Campbell et al, 1994 ;Belaoussoff & Shore, 1995 ;Armbruster, 1996).…”
Section: mentioning
confidence: 99%
“…Such studies have shown among-population correlations between the average amount of herkogamy and outcrossing rates (Rick et al, 1977;Holtsford and Ellstrand, 1992;Belaoussoff and Shore, 1995). Less known is the extent of within-population variation in outcrossing rates and the factors influencing such variation, even though this is one of the primary levels at which natural selection acts.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of hermaphroditic autopolyploid species have mixed mating systems with intermediate or high outcrossing rates (MacDonald and Lieffers, 1991;Husband and Schemske, 1997;Petit et al, 1997;Inoue et al, 1998; but see Murawski et al, 1994). In contrast, selfing is more prevalent in allopolyploids (Belaoussoff and Shore, 1995;Johnston and Schoen, 1996;Cook and Soltis, 1999).…”
Section: Introductionmentioning
confidence: 99%